f(x) = 7-3x
f^(-1)(x) = 1/(7-3x)
so, f^(-1)(2), is just putting x=2 into the above formula, i.e.
f^(-1)(2) = 1/(7-3*2) = 1
2007-05-11 12:07:31
·
answer #1
·
answered by tsunamijon 4
·
0⤊
0⤋
I don't know why you went though all that trouble to upload an image you could have written out, but I digress.
First you have to find the inverse of f(x). Then you have to plug in 2.
To find the inverse, let y = f(x) and solve for x in terms of y.
y = 7 - 3x
y - 7 = -3x
-(y - 7)/3 = x
so f^-1 (x) = -(x - 7)/3, and
f^-1 (2) = -(2 - 7)/3 = -5/3
2007-05-11 19:09:05
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
So, you have the function y = 7 - 3x. To find the inverse, you need to switch the places of y and x and solve for y:
x = 7 - 3y
3y = -x + 7
y = -(x/3) + (7/3)
Then, you plug in 2 for x:
y = -(2/3) + (7/3)
y = 5/3 =]
2007-05-11 20:20:56
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
Let y = 7-3x
To find the inverse:
1). Solve for x
3x = 7-y
x = 7/3 -y/3
2. Swap x and y
y = 7/3 - x/3= f^-1(x)
So f^-1(2) = 7/3 -2/3 = 5/3.
2007-05-11 21:54:53
·
answer #4
·
answered by steiner1745 7
·
0⤊
0⤋
f^(-1) is the inverse of f,
so if f(x) = x + 1, the inverse would be found by:
x = f(x) + 1
f(x) = x - 1
There are many other definitions of inverse functions, but that's the easiest and it works.
f(x) = 7 - 3x
****note: f(x) hereafter is f^-1 (x)
x = 7 - 3 f(x)
x + 3f(x) = 7 - 3 f(x) + 3 f(x)
3 f(x) + x - x = 7 - x
3 f(x) = 7 - x
f(x) = (7 - x)/3
f(2) = (7 - 2)/3
f(2) = 5/3
2007-05-11 19:09:30
·
answer #5
·
answered by eirikir 2
·
0⤊
0⤋
to find the inverse of the function f(x) = 7-3x
rearrange it as follows
f(x) = 7-3x
y = 7-3x
x = (7-y)/3
then f-1(x) = (7-x)/3
so f-1(2) = 5/3 or 1.667
2007-05-11 19:10:48
·
answer #6
·
answered by max 4
·
0⤊
0⤋